THE RELATIONSHIP BETWEEN MATERNAL NUTRITIONAL STATUS AND EXCLUSIVE BREASTFEEDING STATUS WITH INFANT WEIGHT GAIN IN THE SITUBONDO HEALTH CENTER AREA - Nadiro; Paramita, Farah; Supriyadi; Kurniawan, Agung; Wulandari, Alifiah (Journal of Indonesian Specialized Nutrition, 2025)
Background: Infant weight gain is a key indicator for monitoring growth and is influenced by various factors, including maternal nutritional status and breastfeeding practices. Based on the data, it is still found that the low percentage of infants with weight gain and exclusive breastfeeding coverage has not reached the target. This study aims to investigate the relationship between maternal nutritional status and breastfeeding status, with the weight gain of infants aged 1-6 months in the Situbondo Health Center area. Method: This study uses a cross-sectional analytical design involving a sample of 70 breastfeeding mothers with infants aged 1-6 months, selected from 18 posyandu. Data were analyzed using the Chi-square test. Result: The findings showed that 55.7% of infants received exclusive breastfeeding, and 62.9% achieved weight gain in accordance with the Weight-for-Age Growth Curve. There is a significant relationship between breastfeeding status (p = 0.013), maternal nutritional status based on BMI (p = 0.018), and maternal nutritional status based on MUAC (p = 0.001) with infant weight gain. Conclusion: Maternal nutritional status (BMI and MUAC) and exclusive breastfeeding play a key role in supporting optimal weight gain in infants aged 1–6 months.